A stochastic finite element procedure for moment and reliability analysis - Sudret, Bruno; Berveiller, Marc; Lemaire, Maurice (European Journal of Computational Mechanics, 2006)
A new stochastic finite element procedure (SFEP) in the tradition of Ghanem’s work is presented. It allows to deal with any number of input random variables of any type that can model both material properties and loading. The method makes use of Hermite series expansion of the input random variables and polynomial chaos expansion of the response, for which an original implementation is proposed. The link with reliability analysis is also established. Three application examples in geotechnical engineering are given for the sake of illustration. The accuracy and efficiency of SFEP is thoroughly investigated by comparison with well-established approaches.